The Effect of Multiple Representation-Based Scaffolding Strategy in Improving Chemical Literacy - Sunyono, Sunyono; Meristin, Annisa (FKIP Universitas Lampung, 2019)
The effect multiple representation-based scaffolding strategy in improving chemistry literacy. Objective: This study aims tyo understand the effectiveness of multiple representations-based scaffolding strateg in the topics of electrolyte and non-electrolyte solutions to improve the chemistry literacy skills. Method: The research used a quasi-experiment design. The subjects were 78 students of the tenth grade at SMAN 5 Bandar Lampung. The data were analyzed using Tukey test and effect size. Findings: The increase in chemistry literacy abilities of the students in the experimental class was 96.00% influenced by the application of multiple representations learning with scaffolding strategy; meanwhile, it was only 89.00% for control class with no scaffolding. Conclusion: The scaffolding strategy based on multiple-representation in chemistry learning had a high level of effectiveness in improving chemistry literacy skills. Keywords: Effectiveness, scaffolding, multiple representations, chemistry literacy DOI: http://dx.doi.org/10.23960/jpp.v9.i2.201905